PENGARUH PEMBERIAN PUPUK NPK TERHADAP PERTUMBUHAN SEMAI Acacia mangium DI RUMAH KACA - , FEBRIYANI WULANDARI, Ir. Sukirno Dwiasmoro Prianto, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nursery is the most important initial stage of a series of activities of forest refineries. The success of the establishment of a nursery activities will largely determine the success of later stages. To obtain seedlings in the nursery to the purpose it is necessary to fertilization. This study aims to determine the effect of NPK fertilizer on the growth of Acacia mangium seedling age of 1.5 months in the greenhouse. The research was conducted in the Research Center for Biotechnology and Forest Tree Improvement (BBPBPTH), in Purwobinangun, Pakem, Sleman, Yogyakarta, in October to December 2013 parameters observed: Acacia mangium seed germination, seedling height, and percent live. Fertilizer doses given 6 times fertilization is 45 mg, 90 mg, and 135 mg. The research design used was Completely Randomized Design (CRD) with a sample of 13 seedlings for each treatment. The results showed that the NPK fertilizer to seedlings of Acacia mangium age of 1.5 months in the greenhouse had no significant effect on seedling height increment.